Development of a Behavioral Counseling Model Guide with Live Modeling Techniques to Reduce Bullying Behavior - Ni Nyoman Pariani; Dewi Arum Widhiyanti Metra Putri; Nyoman Dantes (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Education at the junior high school level not only aims to develop students' academic competencies but also to foster character development, including moral integrity, independence, and the ability to build healthy social relationships, as mandated by the Pancasila Student Profile through the implementation of the Merdeka Curriculum. However, empirical realities in the field reveal that bullying behaviour both verbal and digital remains widespread, reflecting poor self-regulation and suboptimal internalization of character values among students. This study aims to develop and evaluate the effectiveness of a behavioral counseling guide using the live modeling technique to reduce bullying behavior. The research employed a Research and Development (R&D) approach using the Four-D model (Define, Design, Develop, Disseminate). The participants consisted of 16 seventh-grade students, with expert validators from the fields of guidance and counseling, education, and psychology. Research instruments included a guidebook acceptability questionnaire, a guidebook practicality questionnaire, and a bullying behavior scale all of which were validated for content and reliability. The validation results indicated that the counseling guide was categorized as highly feasible, with an average practicality score of 87%. A limited trial showed significant effectiveness in reducing bullying behavior, with an N-Gain score of 92% in the experimental group and 39% in the control group. The Mann-Whitney test yielded an Asymp. Sig. (2-tailed) value of 0.012, indicating a significant difference between groups. These findings suggest that the behavioral counseling guide utilizing live modeling is both effective and applicable in addressing bullying within the school environment.